SOME SPECIAL FEATURES OF VEDIC INTERPRETATION BY SWAMI DAYANANDA SARASWATI (International Journal of Food and Nutritional Sciences, 2022)
The Vedas are probably the earliest documents of the human mind and it is indeed difficult tosay when the earliest portions of the Vedas came into existence. As the ancient Hindus seldom kept anyhistorical record of their religious, literary and political realizations, it is difficult to determine theperiod of the Vedas with precision. Historians provide us many guesses but none of them is free fromambiguity."1